PRAGMATICS OF TEACHER'S SPEECH IN THE CLASSROOM (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
This article explores the pragmatic aspects of teacher talk within classroom settings, emphasizing how teachers' language use influences communication, learning, and classroom dynamics. Drawing upon speech act theory, politeness principles, and discourse analysis, the study examines various facets of teacher speech, including directives, presuppositions, and the impact of cultural contexts. The analysis is supported by findings from multiple studies conducted across different educational levels and cultural settings. The role of pragmatics in teaching is explored in depth, discussing both theoretical and practical implications for educators in various teaching environments, including EFL (English as a Foreign Language) classrooms, as well as classrooms in multilingual and multicultural settings. In particular, the way that teacher talk interacts with student engagement and classroom behavior is a significant focus of the study.